PERBANDINGAN EFEKTIVITAS HIPOGLIKEMIK OBAT METFORMIN PATEN DAN GENERIK BERLOGO BERDASARKAN PENURUNAN KADAR GLUKOSA DARAH MENCIT (Mus musculus) JANTAN YANG DIINDUKSI ALOKSAN - Aulia Wati; Rachmat Kosman; Assajadda Lizikri (As-Syifaa Jurnal Farmasi, 2014)
Diabetes mellitus (DM) is a group of chronic diseases characterized by increased sugar levels in the blood as a result of disturbances in the body's metabolic system. Comparative studies have been conducted hypoglycemic effect of patent metformin and generic branded metformin to the diabetic male mice with the aim to determine the effect of the patent and the generic branded drug metformin drug in lowering blood glucose levels. This study used male mice were divided into three treatment groups, group I was given Na. CMC as a control, the group II was given generic branded metformin and the group III was given patent metformin. Measurement of blood glucose levels before and after induction of alloxan 120 mg/kgbw intraperitoneally, and for 6 hours after drug administration with measurements every 90 minutes interval. The data obtained were analyzed by ANOVA. The results showed the patents metformin drug have no significantly different effects compared to the generic branded metformin drug.